2015
DOI: 10.1021/acs.chemmater.5b01356
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Electrochemical Properties of Li1–xMn1.5Ni0.5O4 Spinel Cathodes As a Function of Lithium Content and Cation Ordering

Abstract: The electronic and electrochemical properties of the high-voltage spinel LiMn1.5Ni0.5O4 as a function of cation ordering and lithium content have been investigated. Conductivity and activation energy measurements confirm that charge transfer occurs by small polaron hopping, and the charge carrier conduction is easier in the Ni:3d band than in the in Mn:3d band. Seebeck coefficient data reveal that the Ni 2+/3+ and Ni 3+/4+ redox couples are combined in a single 3d band, and that maximum charge carrier concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 45 publications
5
69
1
Order By: Relevance
“…When the C-rate was reduced to C/20, the as-prepared LNMO exhibited a discharge capacity retention of 98%, indicating that the irreversible damage to the material caused by the fast discharge was negligible. The result is comparable to the results of disordered LNMO materials with various particle sizes and morphologies reported in the literature [19,20]. Similar to cycling stability, the rate capability of LNMO materials with octahedral shape and {111} family of planes on the surface was also reported to be superior to that of materials with other particle morphologies [59,61,80].…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…When the C-rate was reduced to C/20, the as-prepared LNMO exhibited a discharge capacity retention of 98%, indicating that the irreversible damage to the material caused by the fast discharge was negligible. The result is comparable to the results of disordered LNMO materials with various particle sizes and morphologies reported in the literature [19,20]. Similar to cycling stability, the rate capability of LNMO materials with octahedral shape and {111} family of planes on the surface was also reported to be superior to that of materials with other particle morphologies [59,61,80].…”
Section: Resultssupporting
confidence: 83%
“…Samples synthesized at temperatures higher than 700 °C exhibit the disordered phase, whereas prolonged annealing at 700 °C favors the formation of the ordered phase [16,20,59]. Kunduraci et al [24] showed that the ordered/disordered phase transition is driven by the oxygen deficiency in the spinel and is accompanied by the formation of a rock salt secondary phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The disordered structure had an extensive solid-solution region during charge M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 and discharge processes and delivered an enhanced rate capability compared to the ordered structure. It can be explained that the enlarged two-phase regions in the ordered spinel have many phase boundaries, imposing the limitation of Li + transport during charge and discharge, whereas the extended solid-solution region in the disordered spinel is beneficial to Li + transport due to the reduced number of phase boundaries that Li + has to overcome [12,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%